Occupational status and nutrition profile and health of public municipal employees - Patrícia Pinheiro de Freitas; Nathália Luíza Ferreira; Ada Ávila Assunção; Iara Barreto Bassi; Aline Cristine Souza Lopes
Abstract Background: Unhealthy lifestyles occur more often in low-socioeconomic status (SES) groups. The assessment of isolated factors reduces the understanding of the problem instead of clarifying the dynamic interaction of these factors in influencing the health. Objective: To study the relationship between nutrition habits and health, and the coexistence of dietary risk factors, according to the occupational status of public municipal employees. Materials and Methods: An electronic epidemiological survey was conducted from September to December 2009. In total, 5,646 public municipal employees (temporary and permanent) of the municipality (14.7%) answered the questionnaire. Sociodemographic information, health, physical activity, nutritional profile, and working conditions related to eating were investigated. Occupational status was defined by the International Socio-Economic Index. The coexistence of dietary risk factors (low consumption of fruits and vegetables, high consumption of chicken skin and meat fat, and insufficient time to eat at work) were evaluated using Venn diagrams. Results: Arterial hypertension, diabetes mellitus and overweight were more frequently reported in the low occupational status, and positive self-reported health was directly related to the occupational status of participants. Conclusion: Differences in health conditions and in the dietary habits of individuals according to occupational status indicate its relevance in the development of public and institutional policies that aim to promote health and reduce inequalities and the need for greater focus on those with lower occupational status.